BDNF receptor TrkB as the mediator of the antidepressant drug action - Casarotto, Plinio; Umemori, Juzoh; Castrén, Eero (Frontiers in Molecular Neuroscience, 2022)
Brain-derived neurotrophic factor (BDNF) signaling through its receptor TrkB has for a long time been recognized as a critical mediator of the antidepressant drug action, but BDNF signaling has been considered to be activated indirectly through the action of typical and rapid-acting antidepressants through monoamine transporters and glutamate NMDA receptors, respectively. However, recent findings demonstrate that both typical and the fast-acting antidepressants directly bind to TrkB and thereby allosterically potentiate BDNF signaling, suggesting that TrkB is the direct target for antidepressant drugs. Increased TrkB signaling particularly in the parvalbumin-expressing interneurons orchestrates iPlasticity, a state of juvenile-like enhanced plasticity in the adult brain. iPlasticity sensitizes neuronal networks to environmental influences, enabling rewiring of networks miswired by adverse experiences. These findings have dramatically changed the position of TrkB in the antidepressant effects and they propose a new end-to-end model of the antidepressant drug action. This model emphasizes the enabling role of antidepressant treatment and the active participation of the patient in the process of recovery from mood disorders.